Women in engineering, 1964 (1964)
1964 1960-2000 "Women in engineering, 1964" [EP0103], 1964 This leaflet, 'Equal pay for equal work: a new deal for women in engineering', was published by the Confederation of Shipbuilding and Engineering Unions in 1964 as part of a claim to the engineering employers for the gradual introduction of equal pay over three years.